Consideration of Vehicular and Pedestrian Flows in A Multi-Modal Traffic Signal Optimization Strategy for Isolated Intersections - Wael Alhajyaseen; Meng LI (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Current signal control strategies tend to ignore the pedestrian delays that may be imposed by reducing traffic delays. Such an objective is reasonable for motorways and rural roads where vehicular traffic is dominant over pedestrian traffic. However, it is not the case in metropolitan cities with large volume of pedestrian demands. This paper developed a traffic signal optimization strategy that considers both vehicular and pedestrian flows. The objective of the proposed model is to minimize the weighted vehicular and pedestrian delays. The deterministic queuing model is used to calculate vehicular traffic delay and pedestrian delay on sidewalk. Pedestrian delay on crosswalk is calculated based on an empirical pedestrian speed model, which considers interactions of pedestrian platoons and their impacts on average walking speed. A Japanese Intersection is utilized as a numerical case study to evaluate the proposed model. MATLAB is used to solve the optimization problem and to output a set of measures of effectiveness (MOEs). The results show that the proposed model improved average person delay (APRD) by 10% without changing the existing cycle length. Moreover, the model can optimize the cycle length and further improve APRD by as much as 44%. In order to demonstrate the applicability of the proposed model for general cases, this paper also conducted sensitivity analysis. The results showed that the proposed model is most significant and necessary for two circumstances: (1) metropolitan areas with high pedestrian demands and (2) major urban arterials with high pedestrian demands crossing major streets.